Efek Perlindungan Saraf dari Ekstrak Metanol Styrax paralleloneurum terhadap Kerusakan Otak yang Diinduksi oleh Etoposide pada Tikus Wistar - Armansyah Maulana Harahap; Indra Priawan; Putri Diannisa Siregar; Muhammad Aldi Rivai Ginting (Indonesian Journal of Medical and Pharmaceutical Science, 2026)
Background: Chemotherapy-induced cognitive impairment (chemobrain) is a significant side effect associated with anticancer agents such as etoposide. This study aimed to evaluate the neuroprotective potential of Styrax paralleloneurum (SP) methanol extract against etoposide-induced oxidative stress in Wistar rats Methods: Adult Wistar rats were randomly divided into six groups (n = 6 per group): normal control, etoposide-treated group (45 mg/kg), etoposide combined with SP at doses of 200, 300, and 400 mg/kg, and SP control group. Brain tissue homogenates were analyzed for markers of oxidative stress, including nitric oxide (NO), protein carbonyls (PC), superoxide dismutase (SOD), and brain-derived neurotrophic factor (BDNF). Results: Etoposide administration significantly increased PC levels and SOD activity while significantly reducing NO levels, indicating increased oxidative stress in brain tissue. Treatment with SP methanol extract, particularly at doses of 300 and 400 mg/kg, significantly reduced PC and SOD levels and restored NO levels (p < 0.01). No statistically significant differences were observed in BDNF levels among the experimental groups Conclusion: The findings of this study suggest that the methanol extract of Styrax paralleloneurum attenuates etoposide-induced oxidative stress in brain tissue. These results suggest that SP may possess neuroprotective properties and could serve as a potential adjunct strategy to mitigate chemotherapy-induced cognitive impairment